Narrowcasting - Gorgulu, Ş Ahika (Edward Elgar Publishing Ltd., 2025)
Narrowcasting is a form of media casting that serves to target specific audience groups, defined by shared values, preferences, or demographic characteristics. The concept has come into higher prominence as a consequence of the shift from mass to personalized content facilitation, owing to the rapid transformation of new information and communication technologies and the ever-increasing popularity of online social networks. Despite the fact that narrowcasting has existed as an alternative since the early days of broadcasting, the new media ecology has fostered the proliferation of its practice in various contexts and formats. In the context of political communication, narrowcasting has the potential to contribute to the democratization of the content production instruments by encouraging user interaction and engagement not only in media reception but also in content production process. Still, certain challenges remain, as the practice of narrowcasting may result in strengthened in-group allegiances and out-group suspicions due to the users’ self-selection of media channels and messages. © The Editors and Contributors Severally 2025.
Keywords: Audience; Broadcasting; Narrowcasting; Niche journalism; Targeting